Episode Depresi Berat Dengan Gejala Psikotik Pada Wanita Berusia 17 Tahun: Sebuah Laporan Kasus - rizki_novtarina21; Boy K.H, High; Graharti, Risti (CV. Jasa Sukses Abadi, 2025)
Major depressive episodes with psychotic symptoms are a form of major depressive disorder characterized by severe affective symptoms accompanied by delusions or hallucinations. This condition is relatively rare, but is associated with a poorer prognosis, a high risk of recurrence, and an increased suicide rate compared to depression without psychotic symptoms. This case report aims to describe the clinical manifestations, diagnostic process, and management strategies in patients with major depressive episodes accompanied by psychotic symptoms. The patient presented with feelings of depression, sadness, and lack of enthusiasm in performing daily activities for 1 year, which had worsened for 4 months prior to admission to the hospital, since the death of the patient's mother. The diagnosis was established based on a psychiatric interview, mental status examination, and diagnostic criteria from the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Management consisted of a combination of antidepressants and antipsychotics, as well as intensive psychosocial support. This report emphasizes the importance of early detection, accurate diagnosis, and comprehensive management to reduce the risk of complications, improve the patient's quality of life, and reduce the recurrence rate. Thus, this case study is expected to serve as an additional reference in the clinical management of major depressive disorder with psychotic symptoms.